2022
DOI: 10.22541/au.165350523.38411460/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prescribing trends for the same patients with schizophrenia over 20 years

Abstract: BACKGROUND: Recent pharmacoepidemiology data show an increase in the proportion of patients receiving second-generation antipsychotic (SGA) monotherapy, but no studies have analyzed the same patients over a long period of time. Therefore, in this study, we decided to evaluate retrospectively schizophrenia patients with available data for 20 years to see whether the drug treatments in the same patients have changed in the past 20 years. METHODS: The study began in April 2021 and was conducted in 15 psychiatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…This is consistent with a previous study that reported that lithium and carbamazepine were the medications associated with constipation 3 . The biperiden equivalent of total anticholinergic drug in 2021 was smaller than that in 2001, as we previously reported 11 . There was no significance between the initiation of laxative use and the daily dose of anticholinergic drugs in 2021 or 2001.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This is consistent with a previous study that reported that lithium and carbamazepine were the medications associated with constipation 3 . The biperiden equivalent of total anticholinergic drug in 2021 was smaller than that in 2001, as we previously reported 11 . There was no significance between the initiation of laxative use and the daily dose of anticholinergic drugs in 2021 or 2001.…”
Section: Discussionsupporting
confidence: 91%
“…3 The biperiden equivalent of total anticholinergic drug in 2021 was smaller than that in 2001, as we previously reported. 11 There was no significance between the initiation of laxative use and the daily dose of anticholinergic drugs in 2021 or 2001. This is not consistent with a previous study by Lin and their colleagues who reported that a higher dose of anticholinergic drugs was associated with increasing laxative use.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations